Sexual Violence at University: Are Varsity Athletes More at Risk? - Parent, Sylvie; Daigneault, Isabelle; Radziszewski, Stephanie; Bergeron, Manon (Frontiers in Psychology, 2022)
Some studies report that the sport context increases the risk of exposure to sexual violence for athletes. In contrast, others indicate a protective effect of sport participation against sexual violence, particularly among varsity athletes. Studies of sexual violence towards varsity athletes are limited by their failure to include control groups and various known risk factors such as age, graduate level, gender and sexual identity, disability status, international and Indigenous student status, and childhood sexual abuse. The purpose of the present study is to fill in these gaps to determine whether varsity athletes are at greater risk than non-athletes of sexual violence towards them or whether, on the contrary, involvement in a varsity sport is coherent with the Sport Protection Hypothesis. Data for this article come from the ESSIMU study (Enquête sur la Sexualité, la Sécurité et les Interactions en Milieu Universitaire), a broad survey of students, professors, and other employees at six francophone universities regarding sexual violence on university campuses. A total of 6,485 students with complete data on sexual violence, athlete status, and gender were included in the study. From this total, 267 participants identified themselves as varsity athletes. Data were analyzed using a series of logistic regressions on each form of violence using athlete status as a predictor and characteristics associated with sexual violence victimization or distinguishing between varsity athletes and non-athletes as confounding variables. When considering all confounding variables in the regression analyses on four yearly incidence rates of sexual violence, the results revealed that being a varsity athlete did not significantly increase the risk of exposure to sexual violence at university. All considered other variables were more significant predictors of the past year’s risk of sexual violence victimization than athlete status was.